2019
DOI: 10.1371/journal.pone.0222782
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of microRNAs and target genes networks in human abdominal aortic aneurysm tissues

Abstract: BackgroundAbdominal aortic aneurysm (AAA) is a pathological enlargement of infrarenal aorta close to the aortic bifurcation, and it is an important cause of mortality in the elderly. Therefore, the biomarker identification for early diagnosis is of great interest for clinical benefit. It is known that microRNAs (miRNAs) have important roles via target genes regulation in many diseases. This study aimed to identify miRNAs and their target genes involved in the pathogenesis of AAA.MethodsTissue samples were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
1
9
0
1
Order By: Relevance
“…Similar to what occurred in plasma, the results in tissue samples differ among studies. As previously reported [ 10 , 15 , 23 , 44 , 45 ], we have observed a downregulation of miR-133b, miR-29b-3p, and miR-27b-3p in AAA tissue, whereas other authors found them upregulated [ 9 , 46 ]. In the case of miR-21-5p, most studies report an increase in AAA tissue [ 9 , 15 , 22 ], while only one group found a decrease [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…Similar to what occurred in plasma, the results in tissue samples differ among studies. As previously reported [ 10 , 15 , 23 , 44 , 45 ], we have observed a downregulation of miR-133b, miR-29b-3p, and miR-27b-3p in AAA tissue, whereas other authors found them upregulated [ 9 , 46 ]. In the case of miR-21-5p, most studies report an increase in AAA tissue [ 9 , 15 , 22 ], while only one group found a decrease [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
“… hsa-miR-503 Targets Rictor (mTOR complex 2 signaling element), promotes tumor progression [ 69 ], promotes ESCC cell proliferation, migration, and invasion by targeting cyclin D1 [ 73 ], negative regulator of proliferation in primary human cells [ 74 ]. hsa-miR-542 Upregulated in AAA patients [ 42 ]. hsa-miR-548d Associated with schizophrenia [ 75 ].…”
Section: Abdominal Aorta Aneurysm and Control Groups Constructionmentioning
confidence: 99%
“…By combining target prediction and expression modulation analysis, we first demonstrated that circ-FNDC3B directly targeted miR-143-3p, a down-regulated miRNA in AAA tissues. 15) MiR-143-3p has been established as an antitumor factor in multiple cancers, such as pancreatic ductal adenocarcinoma, osteosarcoma, and nasal squamous cell carcinoma. [23][24][25] Previous works also uncovered that several other circRNAs, such as circ_0003998 and circRNA casein kinase 1 gamma 3, acted as potent miR-143-3p sponges in human carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…13,14) MiR-143-3p was underexpressed in abdominal aortic tissues of patients with AAA using miRNA qPCR array analysis. 15) However, the biological function of miR-143-3p in AAA development remains to be elucidated. Moreover, it is still unclear whether the action of circ-FNDC3B in the development of AAA is mediated by miR-143-3p.…”
mentioning
confidence: 99%